Escherichia coli Uses Separate Enzymes to Produce H2S and Reactive Sulfane Sulfur From L-cysteine - Li, Kai; Xin, Yufeng; Xuan, Guanhua; Zhao, Rui; Liu, Huaiwei; Xia, Yongzhen; Xun, Luying (Frontiers in Microbiology, 2019)
Hydrogen sulfide (H2S) has been proposed to have various physiological functions, and it may function through reactive sulfane sulfur. Since the two sulfur forms often coexist, they are normally considered interchangeable. Here, we characterized the production of H2S and reactive sulfane sulfur in Escherichia coli MG1655 and found that they are not readily interchangeable. They are primarily produced from L-cysteine via different enzymes. L-Cysteine desulfhydrases consumed L-cysteine and directly generated H2S. The produced H2S was mainly lost through evaporation into the gas phase, as E. coli does not have enzymes that easily oxidize H2S to reactive sulfane sulfur. L-Cysteine desulfhydrases were also responsible for the degradation of exogenous L-cysteine, which is toxic at high levels. Conversely, L-cysteine aminotransferase and 3-mercaptopyruvate sulfurtransferase sequentially metabolized endogenous L-cysteine to produce cellular reactive sulfane sulfur; however, it was not a major route of H2S production during normal growth or during the metabolism of exogenous L-cysteine by the resting cells. Noticeably, the 3-mercaptopyruvate sulfurtransferase mutant contained less reactive sulfane sulfur and displayed a greater sensitivity to H2O2 than did the wild type. Thence, reactive sulfane sulfur is likely a common cellular component, involved in protein sulfhydration and protecting cells from oxidative stress.